Aesthetic Values in Histopathology: Transforming Scientific Imagery into Artistic Expression for Photography Exhibitions - Ishak, Siti Norfatulhana; Abu Bakar, Ruhil Nadiah; Irwandi (Research in Management of Technology and Business, 2024)
Science and art have always been interrelated. It helps us visualize scientific concepts and explore aesthetic aspects which makes it possible to investigate fields where visual components are essential. Histopathology uses the microscope as a tool for studying tissue diseases, thus offering a chance to combine the two aspects. This study examines the fundamental aesthetics of histopathological photographs and discusses how they can be utilized in photography exhibitions. The objective is to explore the intrinsic beauty of scientific images, thereby surpassing conventional art forms. It demonstrates how these images can elicit an emotional or intellectual response from medical practitioners and other viewers beyond medicine. These pictures show that histopathological photos have distinctive aesthetic qualities that can be used for creative ends; thus, contributing novel ideas to both science and art fields. This premise is therefore supported using theories regarding aesthetics, art interpretations, and philosophy in science.